Cover Image. Issue 11 (November 2016) - Guigueno, Mélanie F.; Sherry, David F.; MacDougall‐Shackleton, Scott A.
Abstract : Cover: The cover image, by Mélanie F. Guigueno et al., is based on the Research Article Sex and seasonal differences in neurogenesis and volume of the song‐control system are associated with song in brood‐parasitic and non‐brood‐parasitic icterid songbirds, DOI:10.1002/dneu.22385 .